New Bipolar Electrosurgical Vessel Sealing Device Provides Improved Performance and Procedural Efficiency - Chambers R; Sarno D; Roweton S (Medical Devices: Evidence and Research)
Rheagan Chambers, Danielle Sarno, Susan Roweton Surgical Research and Development, Surgical Operating Unit, Medtronic, Lafayette, CO, USACorrespondence: Susan Roweton, Email susan.roweton@medtronic.comPurpose: This study compared the performance of the new LigaSure™ XP Maryland Jaw Sealer/Divider (XP Maryland) to that of LigaSure Atlas™ (Atlas) and LigaSure™ Dolphin Tip (Dolphin Tip), two early LigaSure™ (LigaSure) devices characterized by consistent and reliable clinical performance.Methods: Ex vivo bench testing on porcine renal arteries compared burst pressures, seal times, and rates of sticking, incomplete cuts, and charring between XP Maryland and Atlas and between XP Maryland and Dolphin Tip. In vivo acute testing on a porcine model compared thermal spread, seal times, and rates of hemostasis, sticking, and incomplete cuts between XP Maryland and the two early LigaSure devices.Results: Ex vivo, XP Maryland showed a significantly faster mean seal time compared to Dolphin Tip (P < 0.0001) and Atlas (P < 0.0001). XP Maryland had fewer incomplete cuts than Dolphin Tip (P < 0.0001) and fewer sticking incidents than Atlas (P = 0.0019). Atlas had a statistically higher average burst pressure compared to XP Maryland (P < 0.0001). As with ex vivo results, XP Maryland had a significantly faster mean seal time in vivo compared to Dolphin Tip (P = 0.0168) and Atlas (P < 0.0001). Other in vivo results showed XP Maryland had fewer incomplete cuts compared to Dolphin Tip (P < 0.0001) and statistically less lateral thermal spread than Atlas (P = 0.0010). For all other ex vivo and in vivo performance characteristics, no statistically significant differences were found between XP Maryland and the other devices.Conclusion: The study demonstrated the consistent and reliable performance of XP Maryland and the two early LigaSure devices. In addition, the studies showed XP Maryland has some improved performance characteristics when compared to Atlas and Dolphin Tip that may result in improved procedural efficiency and may reduce potential surgical risks.Keywords: LigaSure, radiofrequency energy, electrosurgery